Educação e emancipação : crítica aos fins e ao sentido da educação atual na perspectiva das contribuições freirianas - Cover, Ivania (2011)
The education can be sized up by the purposes that guides it and by the means attributed to the pedagogical action developed. This study aims to explain in what terms the instrumental education and the education guided to the market differentiates itself as the sense and the aims from the education proposed by Paulo Freire and, beyond this, to investigate which are the pedagogical relations that can contribute to define the aims and the sense of education in an emancipated perspective. The bibliographic character gives priority to texts from Paulo Freire, the research constitutes itself by reconstructive and critic dialogue that also happens with the contributes of authors like Gilberto Velho, José Eustáquio Romão, Carlos Rodrigues Brandão, Valter Esteves Garcia and Benno Sander. The text comes from the criticize to the current tendency to establish as priority aims to education the appropriation to the market, what implicates take it as an instrument of maintenance and reproduction of oppressor and anti dialogical relations, in terms adopted by Freire as a bank education. In contraposition, the sense of education proposed by Freire is analyzed supporting itself in the thesis that the education is a political act, that always maintain a potential capable to contribute in a decisive way to the process to emancipation of a man, supported in pedagogical principles of dialogue and consciousness. Finally, it looks for to reconstruct critically indicatives that guide the emancipated education that understand the man as a human being conscious of his/her in not concluded and that he/she has vocation to be more. At the end, this investigation reinforces the thesis that the education has to have as main aim the emancipate of individuals and that the obtaining this sense depends on of a pedagogical practice that consider each human being as a subject capable to act and to change the world